Assessing the Energy Profitability of Biofuels Generated from Coffee Waste via Microwave Pyrolysis - Hui Yi Lim; Brandon Han Hoe Goh; Pui Vun Chai; Chun Kit Ang; Cheng Tung Chong (Chemical Engineering Transactions, 2024)
The potential of coffee waste to be valorised into useful bioenergy is investigated using a continuous microwave pyrolysis rig. Coffee waste of Arabica species was ground and pretreated prior to pyrolysis at elevated temperature under CO2 atmosphere. Valorisation of the coffee waste result in char, liquid, and gaseous products. Analysis shows that biochar yield is highest at 450 °C, while bio-oil recovery peaks at 550 °C. Gaseous product results in highest yield at 650 °C. Energy analysis indicates that biochar contains the highest energy density, while bio-oil's energy density decreased with temperature due to cracking of volatiles. Energy profitability was shown to be negative across all temperatures, with highest deficit at 450 °C due to the formation of non-recoverable products such as water. Higher energy profitability was achieved at 650 °C as more volatiles could be recovered in gaseous form. The study shows that microwave pyrolysis is effective in valorising coffee waste and essential to enhance the energy recovery from coffee waste.